Measuring Investment Skills of Fund Managers - CHUA, Choong Tze (Institutional Knowledge at Singapore Management University, 2007)
This article concerns the measurement of the investment skills of fund managers. A method is proposed that allows for a measurement and comparison of fund managersâ€™ performance across time and asset portfolios. The measure, the â€˜Excess Sharpe Ratioâ€™ (ESR) involves the construction of an appropriate benchmark for each fund manager, and then computing the difference between the Sharpe ratio of the manager and that of the benchmark. This procedure allows for a consistent measure of a manager's investment performance with respect to the relevant asset classes that the manager can invest in at any point in time. Using this measure, it is possible to detect significant persistence of managerial skills of up to 11 years. Also, new light is shed on the relationship of expenses to gross returnsâ€even though firms with higher expenses have higher average gross returns, they in fact achieve this through higher risk-taking. Therefore, their ESR scores and Sharpe ratios are lower than firms with lower expenses.